ADAMTS13 Autoantibodies and Burden of Care in Immune Thrombotic Thrombocytopenic purpura: New Evidence and Future Implications. (September 2022) - Dainese, Cristina; Valeri, Federica; Pizzo, Eleonora; Valpreda, Alessandra; Sivera, Piera; Montaruli, Barbara; Porreca, Annamaria; Massaia, Massimo; Bruno, Benedetto; Borchiellini, Alessandra
The introduction Caplacizumab in the management of Immune thrombotic thrombocytopenic purpura (iTTP) has raised different questions, considering its cost-efficacy and the optimal immunosuppressive treatment (IST) to associate. A retrospective multicenter collection of 42 first iTTP cases was conducted to identify variables associated with a higher burden of care and necessity of an implemented IST with early Rituximab (RTX) rescue. A significant correlation resulted between ADAMTS13 inhibitors (ADAMTS13inh) at diagnosis with total plasma exchange (PEXtot) and PEX needed to achieve clinical response (PEXtoCR, r = 0.46; r = 0.48), along with age (r = - 0.31; r = -0.35), platelet count (r = -0.30; r = -0.30), LDH (r = 0.44; r = 0.41) and total bilirubin (r = 0.54; r = 0.35). ADAMTS13inh also correlated with number of days of hospitalization (DoH, r = 0.44). A significant difference was observed in terms of median ADAMTS13inh titer at diagnosis in patient treated with RTX rescue and those responding to only steroid treatment. Thus, ADAMTS13inh titer resulted a marker of iTTP burden of care, associated with higher number of PEXtot, PEXtoCR, DoH and higher probability of needing RTX rescue to achieve clinical response and could be a useful tool for management of new iTTP cases and an interesting variable to optimize iTTP cases stratification in future Caplacizumab cost-efficacy analysis.